2014
DOI: 10.1673/031.014.69
|View full text |Cite
|
Sign up to set email alerts
|

AedesMosquito Species in Western Saudi Arabia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…This clearly poses a great concern about the possible introduction of new viruses into the Kingdom [Azhar et al, 2016] . Although there have been no reports of Zika infection in Saudi up to now, the current outbreak in South and Central America as well as the heavy travel to Saudi from all over the world may put the Kingdom at the front‐line in the fight against ZIKAV particularly with the high prevalence of Aedes aegypti which is the vector for both Zika and dengue viruses . Furthermore, it is not clear whether other flaviviruses do exist in Saudi Arabia or not mostly because of the limited number of surveillance studies and the lack of systematic screening of patients with unexplained febrile illnesses, thus substantial number of cases may remain undiscovered or unrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…This clearly poses a great concern about the possible introduction of new viruses into the Kingdom [Azhar et al, 2016] . Although there have been no reports of Zika infection in Saudi up to now, the current outbreak in South and Central America as well as the heavy travel to Saudi from all over the world may put the Kingdom at the front‐line in the fight against ZIKAV particularly with the high prevalence of Aedes aegypti which is the vector for both Zika and dengue viruses . Furthermore, it is not clear whether other flaviviruses do exist in Saudi Arabia or not mostly because of the limited number of surveillance studies and the lack of systematic screening of patients with unexplained febrile illnesses, thus substantial number of cases may remain undiscovered or unrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…Such mosquito is widely distributed in Saudi Arabia. It was encountered in eastern region [16][17][18][19][20], southwestern region [27,28,30] and western region [27,32]. Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have shown that the risk of severe disease (haemorrhagic fever and Shock syndrome) is significantly higher during a secondary dengue virus infection than during a primary infection [16] Many protective measures were discussed, including increase awareness about the disease in endemic areas, wearing long covered dressings to cover areas liable for the bites, especially during morning, precautions in hospitals treating patients with DF, eliminating infectious sources as water containers such as flower pots, water storage containers and discarded tires, advices for fashion designers to design the clothes in way that help covering areas liable for bites and promoting it through public figures in the community [17].…”
Section: Discussionmentioning
confidence: 99%